Picking Up the Pieces : The Church and Conflict Resolution in South Africa and Rwanda - Cyuma, Samuel (Book collections on Project MUSE., 2012)
In the final ten years of the twentieth century, the world was twice confronted with unbelievable news from Africa. First, there was the end of Apartheid in South Africa. Who would have thought such a change was possible without bloodshed? But the miracle happened, due to responsible political and church leaders and as a result of the unique processes organized through the Truth and Reconcilation Commission under the leadership of Archbishop Desmund Tutu.The second unbelievable experience from Africa was of a rather different and awfully shocking nature: the mass killings in Rwanda. This event soon developed into a real genocide and created a wave of horror around the world. There, political and church leaders had been unable to prevent this crime against humanity.